Mapping Research Trends in Mathematical Communication: A Bibliometric Review Using VOSviewer - Zulaika Daningtyas; Nizlel Huda; Syamsir Sainuddin (MASI Mandiri Edukasi, 2025)
This study aims to examine the development and trends of research on mathematical communication indexed in the Scopus database through a bibliometric analysis using VOSviewer. Data were collected using the keyword “mathematical communication” for the period 2015–2025, resulting in 431 relevant documents and 53 terms grouped into three main clusters. The metadata were exported in RIS format and analysed to map author collaboration, keyword networks, citation patterns, and research development trends. The findings show that most publications are journal articles, with Indonesia contributing the largest share, particularly through the Infinity Journal. The publication trend reveals a fluctuating pattern with significant growth since 2023, indicating rising global interest in mathematical communication research. The analysis identifies emerging clusters on mathematical representation, RME-based instruction, and multimodal communication. Importantly, the findings highlight how mathematical communication research underpins 21st-century pedagogical innovation by linking communication, reasoning, and technology-enhanced learning. Furthermore, the study identifies research gaps in digital communication models and cross-national collaboration, highlighting the need for stronger international partnerships and theoretical integration to advance the field. By mapping this evolving domain, the study provides insights that can inform educators and policymakers in enhancing communication-centred mathematics curricula and promoting globally connected research initiatives.